Intravitreal Use of a Bone Marrow Mononuclear Fraction (BMMF) Containing CD34+ Cells in Patients with Stargardt Type Macular Dystrophy - Carina Costa Cotrim; André M. Vieira Messias; Rodrigo Jorge; Rubens Camargo Siqueira (Stem Cells International)
To assess the therapeutic potential and the safety of intravitreous use of a bone marrow mononuclear fraction (BMMF) containing CD34+ cells in patients with Stargardt type macular dystrophy. The study was conducted on 10 patients with Stargardt dystrophy with worse eye visual acuity≤20/125. A bone marrow aspirate was obtained from all patients, and after processing in the cell therapy center (CTC), 0.1 ml of the intravitreous BMMF suspension was injected into the eye with worse visual acuity. A sham injection was performed in the contralateral eye. The patients were evaluated at baseline and one, three, and six months after the injection. All of them were submitted to measurement of best corrected visual acuity (BCVA), microperimetry, multifocal electroretinography (mfERG) and full field electroretinography (ffERG), autofluorescence (AF), and optical coherence tomography (OCT). Fluorescein angiography was also performed before and six months after the injection. All patients completed the six-month period of evaluation. Mean visual acuity of the treated eye was 1.1 logMAR (20/250) before intravitreous (IV) injection, 0.96 logMAR (20/200+2) one month after injection, and 0.92 logMAR (20/160-1) 3 months after injection. In the untreated eye, mean VA was 1.0 logMAR (20/200) at baseline and 0.96 logMAR (20/200+2) and 0.94 logMAR (20/160-2) one and three months after injection, respectively. In the treated group, VA at baseline ranged from best acuity of 20/125-1 to worst acuity of 20/640+2, going through 20/100+2 and 20/400 during the first month. In the untreated group, BCVA ranged from 20/100+2 to 20/400 at baseline and from 20/100 to 20/400 after one month. The results for the treated group differed significantly at all follow-up times, whereas no significant difference was observed in the untreated group. Regarding the mean sensitivity of microperimetry, although there was improvement throughout all months, a significant difference occurred only during the first month. In the untreated eye, there was no significant difference in any analysis. Angiofluoresceinography did not reveal neovessel formation or tumor growth. The remaining exams were used in order to aid the diagnosis. The results indicate that the use of intravitreous BMMF in patients with Stargardt dystrophy is safe and is associated with a discrete improvement of BCVA and microperimetry in the treated eye compared to the untreated one.